Two new species and a new record of Lecanora sensu stricto (Lecanoraceae, Ascomycota) from India - Papong, Khwanruan; Nayaka, Sanjeeva; Lumbsch, H. Thorsten (Phytotaxa, 2012)
The new species Lecanora girigangaensis and L. upretii from Himachal Pradesh in India are described. The former has large apothecia with a constricted base, melacarpella-type amphithecium, glabrata-type epihymenium, hyaline hypothecium, and contains atranorin and usnic acid, while the latter is characterized by having yellow-brown to pale brown apothecial discs, a melacarpella-type amphithecium, pulicaris-type epihymenium, and contains atranorin and usnic acid. Also, Lecanora subalbellina is recorded from Asia for the first time.